Occupational risks of hospital nursing professionals: socio-demographic and labor profile (Research, Society and Development, 2022)
Objective: to trace the socio-demographic and work profile of nursing professionals. Method: study with quantitative, exploratory and descriptive approach. Held in a Public And Teaching Clinic Hospital. A total of 60 nursing professionals were interviewed and a socio-demographic work questionnaire was applied. The data were collected in October, November and December 2021, graphs and tables were created, the G-independence test and the chi-square test were used, both with significance value for p